THE MARKET RISK ANALYSIS BY QUANTIFICATION METHOD - CONSTANTIN ANGHELACHE; MĂDĂLINA-GABRIELA ANGHEL; ȘTEFAN VIRGIL IACOB (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2020)
In this article, the authors aimed to establish the concrete econometric ways in which market risk can be determined and based on the calculated parameters can be estimated. This study starts from the concrete situation of the occurrence of market risk which is obvious in the conditions in which they appear disturbed from one period of time to another. Through the data available to them, the authors identified and highlighted the advantages of the quantification method, in fact the only method to establish in concrete terms a system of equations on the basis of which to obtain the parameters, which can then be used in estimating market developments in the context of risk. The article comprises a series of calculation relations, some data being introduced in these relations and established, then in equations to underlie the calculations performed. The article has a more theoretical character because it starts from the specialized literature and ensures the implementation of a generally valid method of quantification.